Design, Modelling and Simulate of DC motor for Robotics to Enhance Speed and Direction (The International Journal for Scientific Research, 2025)
The present research seeks to elucidate the design and execution of a bidirectional control system for DC motors, employing the Arduino UNO microcontroller and the L293D motor driver. Offering a cost-effective, user-friendly solution for precise speed and direction control in robotics, automation, and industrial applications. The methodology integrates the L293D’s dual H-bridge configuration for bidirectional control through voltage polarity reversal and employs Pulse Width Modulation (PWM) via Arduino to adjust motor speed by varying the duty cycle (0–255), the mathematical model linking input voltage to motor speed is embedded in the Arduino programming environment (Micro C) to ensure accurate speed modulation for this purpose use Simulations in Proteus 8 Professional validate the circuit design and control logic, followed by physical prototyping to real-world functionality, the Experimental results demonstrate seamless transitions between clockwise, anticlockwise, and braking modes, with PWM enabling linear speed adjustments (0–12V) and the L293D providing robust protection against overcurrent and thermal overload. The system achieves a 40% cost reduction compared to traditional setups while maintaining reliability under variable loads, offering instantaneous directional switching and smooth speed transitions, this work underscores the practicality of combining Arduino microcontrollers with the L293D driver for efficient DC motor control, adaptable to educational, industrial, and consumer electronics contexts. The investigation advocates for broader adoption in energy-efficient automation and IoT-enabled frameworks, emphasizing scalability, simplicity, and real-world applicability.
Keywords: IoT Integration; Direct-Current (DC) Motor; Arduino-L293D Framework; Remote Accessibility; Protous Program